2015
DOI: 10.3201/eid2103.140209
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Microepidemics among Dispersed Migrants, Birmingham, UK, 2004–2013

Abstract: To determine if local transmission was responsible for rising tuberculosis incidence in a recently dispersed migrant community in Birmingham, UK, during 2004–2013, we conducted enhanced epidemiologic investigation of molecular clusters. This technique identified exact locations of social mixing and chains of apparent recent transmission, which can be helpful for directing resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…In such a situation, identical MIRU-VNTR typing will be wrongly interpreted as recent transmission in the country of immigration (9). Similar observations were made in the United Kingdom, where immigrant TB patients were identified in transmission clusters on the basis of standard MIRU-VNTR genotyping, although no epidemiological link could be found during contact investigations (16).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In such a situation, identical MIRU-VNTR typing will be wrongly interpreted as recent transmission in the country of immigration (9). Similar observations were made in the United Kingdom, where immigrant TB patients were identified in transmission clusters on the basis of standard MIRU-VNTR genotyping, although no epidemiological link could be found during contact investigations (16).…”
Section: Discussionsupporting
confidence: 52%
“…However, MIRU-VNTR typing may not distinguish between genetically closely related strains despite the absence of close epidemiological links between patients (16)(17)(18). MIRU-VNTR typing may be suboptimal for studying transmission among immigrants from countries with a high TB incidence, where genetically closely related strains circulate over extended periods of time (19).…”
mentioning
confidence: 99%
“…In addition, we sought undiscovered latent TB infection cases by using interferon-γ release assays to find patient contacts in unsuspected settings. Given that earlier studies performed similar investigations and found latent and active TB cases ( 8 , 9 , 11 ), a combination of population-based molecular typing and further contact investigation is expected to be an effective strategy for discovering unknown latent TB infections or active TB cases. Moreover, we examined links in detail for 57 patients infected with M. tuberculosis strains in the SLV group; our findings confirmed epidemiologic links in 21.1% (12/57) of the cases (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…In summary, molecular genotyping methods make it possible to perform evidence-based TB control ( 8 11 , 27 ). We confirmed the effectiveness of these methods in a mostly elderly population by using VNTR typing with in-depth contact tracing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation